On the centrifugal granulation characteristics by rotary disk: Effect of outer edge structure. (August 2019) - Tan, Yu; Wang, Hong; Zhu, Xun; Lv, Yiwen; He, Xianyan; Liao, Qiang
Graphical abstract: The side wall adhesion phenomenon was observed for the flat edge disk during centrifugal granulation process. The underlying reason for the adherence was theoretically analyzed and ascribed to the intricate trade-off between centrifugal force and surface tension. The flat edge disks contribute to larger critical flowrate and smaller droplet size. Highlights: The disk edge was found with considerable impact on the liquid film movement and granulation. The critical volume flow rate was enhanced significantly by the flat edge disk. Smaller droplets were produced by the flat edge disk. The long flat edge disk is suggested to granulate the low viscous liquid. The short flat edge disk is recommended to granulate the high viscous liquid. Abstract: Atomizer configurations are pivotal for centrifugal granulation to recovery heat recovery from high-temperature blast furnace slag. In this study, water and water/glycerol mixtures were selected as the working medium analogizing to real molten blast furnace slag. We visualized their granulation processes on five sets of disks with long-flat (LF), short-flat (SF), sharp (S), trapezoid (T) and circular (C) edges. The disk edges are found with considerable impact on the liquid film movement: the LF- and SF-edge disks allow for the adherence of liquid film on the side walls while the rest disks suppress such adherences. The underlying reason for the adherence was theoretically analysed and ascribed to the intricate trade-off between centrifugal force, surface tension and adhesion force. Indicators including adherence distance, critical flowrate and droplet size were considered to assess these disks. The LF- and SF-edge disks contribute to larger critical flowrate and smaller droplet size compared to S-, T- and C-edge disks. The present study shed light on the effect of disk edges on granulation characteristics and provides new insights into atomizer design towards better granulation performance of blast furnace slag.